Breast cancer stem-like cells are inhibited by a non-toxic aryl hydrocarbon receptor agonist. - Gérald J Prud'homme; Yelena Glinka; Anna Toulina; Olga Ace; Venkateswaran Subramaniam; Serge Jothy (PLoS ONE, 2010)
Cancer stem cells (CSCs) have increased resistance to cancer chemotherapy. They can be enriched as drug-surviving CSCs (D-CSCs) by growth with chemotherapeutic drugs, and/or by sorting of cells expressing CSC markers such as aldehyde dehydrogenase-1 (ALDH). CSCs form colonies in agar, mammospheres in low-adherence cultures, and tumors following xenotransplantation in Scid mice. We hypothesized that tranilast, a non-toxic orally active drug with anti-cancer activities, would inhibit breast CSCs.We examined breast cancer cell lines or D-CSCs generated by growth of these cells with mitoxantrone. Tranilast inhibited colony formation, mammosphere formation and stem cell marker expression. Mitoxantrone-selected cells were enriched for CSCs expressing stem cell markers ALDH, c-kit, Oct-4, and ABCG2, and efficient at forming mammospheres. Tranilast markedly inhibited mammosphere formation by D-CSCs and dissociated formed mammospheres, at pharmacologically relevant concentrations. It was effective against D-CSCs of both HER-2+ and triple-negative cell lines. Tranilast was also effective in vivo, since it prevented lung metastasis in mice injected i.v. with triple-negative (MDA-MB-231) mitoxantrone-selected cells. The molecular targets of tranilast in cancer have been unknown, but here we demonstrate it is an aryl hydrocarbon receptor (AHR) agonist and this plays a key role. AHR is a transcription factor activated by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), polycyclic aromatic hydrocarbons and other ligands. Tranilast induced translocation of the AHR to the nucleus and stimulated CYP1A1 expression (a marker of AHR activation). It inhibited binding of the AHR to CDK4, which has been linked to cell-cycle arrest. D-CSCs expressed higher levels of the AHR than other cells. Knockdown of the AHR with siRNA, or blockade with an AHR antagonist, entirely abrogated the anti-proliferative and anti-mammosphere activity of tranilast. Thus, the anti-cancer effects of tranilast are AHR dependent.We show that tranilast is an AHR agonist with inhibitory effects on breast CSCs. It is effective against CSCs of triple-negative breast cancer cells selected for anti-cancer drug resistance. These results suggest it might find applications in the treatment of breast cancer.